NILAI-NILAI PENDIDIKAN ISLAM DALAM SERIAL ANIMASI HAFIZ HAFIZAH DAN RELEVANSINYA PADA MATERI PAI KELAS V SD - Savina Aulia Azzahra; Sokhibul Arifin; Ika Puspitasari (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This study aims to determine the values of Islamic religious education in the animated film series Hafiz Hafizah and to relate them to Islamic education material for grade V SD. This study uses qualitative methods and the type of research is Library research by randomly selecting 5 episodes by the researcher. The results of this study indicate that the values of Islamic religious education in this film are as follows: 1) having faith in the Apostle by behaving tabligh in the episode